Kado buat yang sedang sakit / Mohamad Zaenal Arifin, Idnan A. Idris, Yati Priyati; editor, DW. Goenawan - MOHAMAD ZAENAL ARIFIN 1978-; IDNAN A. IDRIS; YATI PRIYATI; GOENAWAN, DW. (Yayasan Masjid at-Taqwa, 2017)
xi, 196 halaman ; 20 cm.